The Problem of Unavailability of Living For Low-Income Communities in Pekunden Rental Flats: Masalah Tidak Tersedianya Tempat Tinggal Bagi Masyarakat Berpenghasilan Rendah di Rusun Sewa Pekunden - Arvante, Jeremy Zefanya Yaka; Irawaty, Irawaty (Faculty of Law, Universitas Negeri Semarang, 2024)
Rental flat was built to facilitate low income communities to obtain temporary housing. However, the implementation of the flats was not on target because people who were unfit to live in the Pekunden flats were not disciplined by the UPTD. The legal umbrella for condominiums is contained in Law no. 20 of 2011. Likewise, flats in Semarang City have rules for implementing flats which are regulated in Mayor Regulation No. 7 of 2009. The aim of this research is to identify and analyze the implementation of the rental extension of the Pekunden Rental flat Mayor Regulation of Semarang City No. 7 of 2009 and find out and analyze what repressive efforts there are regarding the problem of unavailability of housing for low income communities in the Pekunden flats.The results of the research carried out were that the Semarang City Government in carrying out the provision of flats did not implement Law no. 20 2011, in practice there are still well-off flat residents living in flats. The conclusion and suggestion from this research is that in implementing the flats, the Semarang City Government does not confirm the termination time for residents to settle. This problem causes the low income communities queue list for Pekunden flats to increase and they never get their rights, so it is necessary to implement implementing regulations regarding termination times and special qualifications for lease extensions by Disperkim or discretion by UPTD. Regarding this problem, repressive efforts must also be found to overcome it.